Examining Hybrid Learning Perceptions of Accounting Students Using Technology Acceptance Model - Ali, Mazurina Mohd; Ghani, Erlane K; Bakar, Y Nurli Abu; Aziz, Maz Ainy Abdul; ., Pujiono; Hidayat, Rendra Arief; Dwinda, Merlyana (Journal of Ecohumanism, 2024)
This study investigated accounting students' perceptions of hybrid learning, examining its usefulness, acceptance, and factors influencing its adoption. The post-pandemic period offers a unique opportunity to understand how students perceive technology-enhanced education, particularly hybrid learning. The study employed the Technology Acceptance Model (TAM) to analyze students' attitudes toward technology in accounting education. By focusing on accounting students who require practical skills alongside theoretical knowledge, the study aimed to provide insights for strategic planning in university teaching. The findings would contribute to the ongoing improvement of accounting practices and the future of accounting education in response to crises.